2020
DOI: 10.1155/2020/6956402
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Workers Exposed to Volatile Organic Compounds Associated with Different Occupations by Headspace GC-FID

Abstract: The present study has been undertaken to analyze the total accumulated burden of volatile organic compounds (VOCs) in blood of occupationally exposed workers. The headspace technique combined with gas chromatography with flame ionization detector was used for the quantitative analysis of the different volatile organic compounds (isopropyl alcohol, phenol, benzene, dichloromethane, ethanol, ethyl acetate, and toluene) in 80 blood samples from the workers belonging to different occupations i.e., shoe polish work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…In concordance with this conclusion, a recent study showed that alcohols are the most prevalent class of VOCs in the printing industry (Alabdulhadi et al, 2019). In addition, a recent report has determined quantitatively different volatile organic compounds from blood samples from printing press workers and has evidenced higher concentrations of ethyl alcohol and isopropyl alcohol than other VOCs (Yaqub et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
“…In concordance with this conclusion, a recent study showed that alcohols are the most prevalent class of VOCs in the printing industry (Alabdulhadi et al, 2019). In addition, a recent report has determined quantitatively different volatile organic compounds from blood samples from printing press workers and has evidenced higher concentrations of ethyl alcohol and isopropyl alcohol than other VOCs (Yaqub et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
“…To quantify the trace quantity of metabolites, researchers usually coupled the skin sampling devices to highly sensitive equipment like Gas Chromatography-Flame Ionization Detector (GC-FID), 24,25 Gas Chromatography-Mass Spectrometry (GC-MS), 26,27 Gas Chromatography Time-of-Flight Mass Spectrometry (GC-TOF-MS) and electronic nose (e-nose). 28,29 GC-FID is primarily utilized to determine the hydrocarbons and other volatile organic compounds from the skin.…”
Section: Chiranjit Ghoshmentioning
confidence: 99%
“…Yaqud et al (15) Biomonitoring of workers exposed to volatile organic compounds associated with different occupations by headspace GCFID.…”
Section: Sarpullido 422mentioning
confidence: 99%
“…(18,19) La mayor parte de solventes orgánicos son considerados contaminantes ambientales, uno de estos; el benceno, posee una elevada volatilidad y composición peligrosa para la salud, la entrada al cuerpo humano se da por absorción cutánea provocando quemaduras en la piel, irritación oftálmica, existe un daño mucho más crónico en personal encargado de despachar gasolina incluyendo efectos adversos a nivel de sistema nervioso central, hepático y renal. (15,20,21) Montano (9) menciona que existe un alto número de estudios epidemiológicos sobre dermatopatías en países europeos. Afirma que las en mayor parte las patologías profesionales se deben a dermatitis de contacto irritante, alergias de contacto preferentemente a nivel de miembros superiores y la cara.…”
Section: Quemaduras -unclassified
See 1 more Smart Citation